Competências socioemocionais no serviço público: Um estudo com gerentes de atendimento do INSS - Macêdo, José Wilker de Lucena (2019)
The aim of this research is the analyze the Social and Emotional Competencies (SEC) of managers of Social Security Agencies (SSA). The theoretical framework was divided in three parts: a managerial action in the public sector, as managerial competences in the public service and the social and emotional competences. This last part is divided in the subsections: measurement of the CSE construct and the need for a scale to measure the CSE construct of managers. The methodology of this work has a qualitative, exploratory and descriptive approach, and it is divided in two stages: the group interview by a focus group and the application of a survey. The research was developed together with APS managers. In the first stage 16 managers participated and in the second stage 424 servers in management positions answered the questionnaire. The data obtained in the first stage were analyzed comprehensively and interpretatively, while the data of the stage were quantitative using SPSS and R software, which allowed the accomplishment of correlation analysis, reliability and confirmatory and exploratory factorial . The performance difference between the working and managerial groups may be more experienced and less experienced through the non-parametric Mann-Whitney test. The main result of this work was the validation of a scale to measure as CSE of APS managers. Some differences between groups for the socioemotional competences defined in the scale (emotional awareness, emotional regulation, teamwork, self-control and emotional creativity) are verified. The final scale has 25 items and can be validated in other professional contexts.